Experimental evidence that matching habitat choice drives local adaptation in a wild population. Issue 1927 (27th May 2020) - Camacho, Carlos; Sanabria-Fernández, Alberto; Baños-Villalba, Adrián; Edelaar, Pim
Abstract : Matching habitat choice is a unique, flexible form of habitat choice based on self-assessment of local performance. This mechanism is thought to play an important role in adaptation and population persistence in variable environments. Nevertheless, the operation of matching habitat choice in natural populations remains to be unequivocally demonstrated. We investigated the association between body colour and substrate use by ground-perching grasshoppers ( Sphingonotus azurescens ) in an urban mosaic of dark and pale pavements, and then performed a colour manipulation experiment to test for matching habitat choice based on camouflage through background matching. Naturally, dark and pale grasshoppers occurred mostly on pavements that provided matching backgrounds. Colour-manipulated individuals recapitulated this pattern, such that black-painted and white-painted grasshoppers recaptured after the treatment aggregated together on the dark asphalt and pale pavement, respectively. Our study demonstrates that grasshoppers adjust their movement patterns to choose the substrate that confers an apparent improvement in camouflage given their individual-specific colour. More generally, our study provides unique experimental evidence of matching habitat choice as a driver of phenotype–environment correlations in natural populations and, furthermore, suggests that performance-based habitat choice might act as a mechanism of adaptation to changing environments, including human-modified (urban) landscapes.